The Effect of middle ear volume on hearing improvement post myringoplasty - Yusof, Asfa Najmi Mohamad (2017)
Tympanic membrane perforation (TMP) is one of the features of CSOM. It is surgically corrected with myringoplasty. Successful myringoplasty referred to a completely healed tympanic membrane and may resulted in hearing improvement post operatively. Besides TMP, middle ear volume (MEV) is another factor that has been shown quite recently to affect hearing loss and thus is thought to play a role in hearing improvement post myringoplasty. This study aims to determine whether MEV does have an important role in the hearing improvement post myringoplasty. A total of 72 CSOM patients who underwent myringoplasty and resulted with healed TM were evaluated. Audiometric tests were performed pre- and 3 months postoperatively. Pure tone audiometry (PTA) was done to determine the level of hearing improvement and improved hearing was recorded as average difference air bone gap (ABG) pre and post-operatively. While tympanometry was done to determine the MEV. The mean MEV was measured and divided into small and large groups.Perforated eardrums were examined and photographed through a system of 'endoscopic' or drawing. The size of TMP was recorded in percentage and then divided into 3 groups; small <50%, moderate 50-75% and > 75%. Data analysis showed hearing improvement post myringoplasty in all frequencies, particularly at low frequencies. ABG pre-operative was 27.58 dB and post-operative was 14.33 dB. The ABG difference showed hearing improvement of 13.25 dB. Mean MEV in this study was 2.83 ml. MEV was found not to have any affect on the hearing improvement post myringoplasty. Moreover, the size of perforated tympanic membrane measured pre-operatively also did not affect hearing outcome post myringoplasty. Lastly, there was no significant correlation between those 2 factors on hearing improvement post myringoplasty. Objective To determine whether the middle ear volume affecting hearing improvement post myringoplasty. Study design This is a prospective observational study in Otorhinolaryngology Clinic and Hospital Universiti Sains Malaysia Hospital Raja Perempuan Zainab II.Methodology xii 72 subjects of CSOM patients who fulfilled the criteria were selected to participate in this study. Patients aged 15 years and above, conductive hearing loss and surgical planning for myringoplasty were included in this study. However, we excluded patients with hearing loss greater than 50 dB, mucopurulent ear discharge and unhealed tympanic membrane after surgery. Written consent for this study were obtained from the patient. All information regarding the patient’s detail, physical examination and hearing tests were recorded. PTA was performed to determine the level of hearing improvement and tympanometry to determine the MEV before and 3 months after surgery. Improved hearing recorded is the average difference ABG pre and post-operatively in 250, 500, 1000, 2000 and 4000Hz frequencies. The mean MEV divided the volume into small and large groups. A perforated eardrum examined and photographed through a system of 'endoscopic' or drawing. Percentage of size of TMP was recorded and divided into 3 groups; small <50%, moderate 50- 75% and > 75% were recorded. Conclusion Closure of TMP had resulted in significant hearing improvement in all frequencies. However, both size of perforation and MEV showed no effect on hearing improvement post myringoplasty. There is no correlation between them.